The Effectiveness of Using Beginner-Level Indonesian Language Textbooks to Improve Vocabulary Understanding for Arabic Speakers - Mohammad Ahsanuddin; Nurul Murtadho; Nur Anisah Ridwan; Norasyikin Osman; Najma Auliya' Maulidah Ahsan (Nexus Publishing, 2025)
The purpose of this study was to describe (1) a beginner-level Indonesian language textbook for Arabic speakers, (2) the effectiveness of a beginner-level Indonesian language textbook to improve Arabic speakers' vocabulary comprehension. This study was a type of experimental research before the experiment involving a single-group pretest-posttest design. The results showed that (1) this beginner-level BIPAR book consists of five chapters covering important topics in daily life, such as introductions, family, daily activities, traveling, and food and drinks, (2) The pretest results showed that the average initial ability of participants was below the expected standard (average score of 48.07 with the highest score of 87 and the lowest score of 20). However, after learning using the BIPAR book, the posttest results showed a significant increase with an average score of 84.20 (the highest score of 100 and the lowest score of 67). This increase reflects the effectiveness of the textbook in improving participants' understanding. The results of the statistical test using the paired sample t-test method showed a significant difference between the pretest and posttest scores. With a t-count value of -9.668 which is greater than the t-table, and a significance value of 0.000, the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. This shows that the use of the BIPAR Beginner Level textbook has a significant influence in improving the language skills of training participants.